Molecular Epidemiology of New Delhi Metallo-β-Lactamase-Producing Escherichia coli in Food-Producing Animals in China - Kuang, Xu; Zhang, Yan; Liu, Juan; Yang, Run-Shi; Qiu, Zhi-Ying; Sun, Jian; Liao, Xiao-Ping; Liu, Ya-Hong; Yu, Yang (Frontiers in Microbiology, 2022)
We conducted a molecular surveillance study for carbapenem-resistant Enterobacteriaceae (CRE) colonization in food-producing animals in China that included primarily swine and poultry for three consecutive years. A total of 2,771 samples from food-producing animals and their surrounding environments were collected from different regions in China from 2015 to 2017. Enrichment cultures supplemented with meropenem were used to isolate carbapenem non-susceptible isolates and these were subsequently identified by MALDI-TOF MS. Resistance phenotypes and genotypes were confirmed using antimicrobial susceptibility testing and molecular biological techniques. Genomic characteristics of the carbapenemase-producing isolates were investigated using whole genome sequencing (WGS) and bioinformatic analysis. In total, 88 NDM-positive Enterobacteriaceae were identified from 2,771 samples and 96.6% were Escherichia coli. The New Delhi metallo-β-lactamase (NDM)-positive E. coli displayed a diversity of sequence types (ST), and ST48 and ST165 were the most prevalent. Three variants of blaNDM (blaNDM-1, blaNDM-4, and blaNDM-5) were detected and WGS indicated that blaNDM-5 predominated and was carried primarily on IncX3 plasmids. All these isolates were also multiply-drug resistant. These results revealed that food-producing animals in China are an important reservoir for NDM-positive E. coli and pose a potential threat to public health.